A Practical Perspective on Airport Demand Management - FAN, Terence Ping Ching (Institutional Knowledge at Singapore Management University, 2002)
This paper explores demand management policies for airport capacity allocations. While regulatory mechanisms to limit access and reduce congestion are in place in most major airports overseas, the U.S. policy is still evolving. The experiment in 2001 at New York's La Guardia is examined for its implications at other facilities. The lottery allocating landing slots was deemed a success at reducing passenger delays. The evidence also suggests that access to landing slots is under-priced at most U.S. facilities. But future policies also have to take into account other elements in addition to the purely economic ones, such as sustaining operations and access to the airspace system in smaller communities, general aviation users, new entrants and others who are at risk of being locked out in any comprehensive, purely market-driven scheme.